Radiation-induced changes in infra-red spectrum of black zinc diphosphide monocrystals - Kudin, A.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
For the first time the effect of ionizing particles of different type (gamma-quanta, electrons) and neutrons upon infra-red spectra of zinc diphosphide has been studied. It was shown that the defects of phosphorus sublattice, that are the principal centers of optical activity in the infra-red (IR), are responsible for structural evolution of zinc diphosphide crystals in the process interaction with radiation of different types.